El modo de ser aristocrático. El caso de la oligarquía chilena hacia 1900 - Vergara, Ximena (Ariadna Ediciones, 2007)
Detailed description of the lifestyle of groups of high Chilean society in the late 19th and early 20th century, and its social and political role